Peran Ekonomi Manajerial Dalam Mengidentitifikasi Dan Mengurangi Inefisensi Akibat Korupsi Proyek Gerobak Usaha Mikro Kecil Dan Menengah - Laila Karima Hakim; Sania Amalia; Damar Reymoza; Pupung Purnamasari (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
In every nation, Micro, Small, and Medium Enterprises (MSMEs) are a top priority for development. This is because MSMEs have made significant contributions to the nation, particularly in the social and economic spheres. MSMEs are crucial for absorbing workers from the unorganized sector and balancing community income, particularly in the areas, in addition to boosting the nation's economic progress. Nevertheless, the Ministry of Trade (Kemendag) received concerns from the public about the trading cart support program. has not been delivered. After learning of this, it was discovered that commerce had engaged in corruption in the purchase of MSME carts. both in 2018 and 2019. Everyone should be concerned about corruption since it is a worldwide issue. The idea of a totalitarian government, which is a dictatorship in which a small number of people hold all the power, is typically associated with corrupt behaviors. A totalitarian power structure makes it difficult for the media and society to uncover such corrupt behaviors. A democratic style of governance offers the best chance to reveal corrupt practices. Because avaricious political and economic elites band together to take advantage of Indonesia's natural resources for their own benefit, corruption has a significant negative influence on the environment. It also continues to have a significant negative impact on other areas, including politics, democracy, education, and community life. The waste of money, time, and resources brought on by corrupt activities is referred to as inefficiency brought on by corruption. The declining quality of goods and services is one example of corruption-related inefficiency. In order to cut expenses and increase personal benefit, corruption frequently entails lowering requirements or fabricating reports. Infrastructure, public services, or subpar products are affected, leading to their rapid destruction or inefficiency. Furthermore, in order to cut expenses and increase personal benefit, corruption frequently entails lowering standards or fabricating reports. Infrastructure, public services, or subpar products are affected, leading to their rapid destruction or inefficiency. Identifying and minimizing inefficiencies in the "trading cart assistance program for Micro, Small and Medium Enterprises (MSMEs) by the Ministry of Trade (Kemendag)" is the goal of this study. utilizing managerial economics and the Cost-Benefit Analysis method to determine the case.